Customers perception towards marketing programs of POSLAJU: Klang Valley area / Nor Marini Mohtar - Mohtar, Nor Marini (Faculty of Business and Management, 2007)
The purpose of this research is to study the customer perceptions towards the marketing programs in terms of product, price, place, promotions and corporate image. Moreover this study will identify customer awareness, expectations and satisfactions towards POSLAJU as well as their relationship. Therefore the objectives of this research are: 1) To study the effectiveness of current marketing programs that has been implemented by POSLAJU. 2) To identify the level of customer awareness and expectation towards marketing program of POSLAJU. 3) To determine the level of customer satisfaction towards marketing program of POSLAJU. 4) To provide suggestion and recommendation on certain action to be taken by POSLAJU to enhance their marketing program to be more competitive in future. In this study, we used interviews and questionnaire to identify the relevant aspect regarding the study on the customers at POSLAJU in Klang Valley area and others secondary sources such as reports, database and so on. The total respondents that involved in this study are 80 respondents. For the sampling technique, nonprobablity sampling have been using for this study. Based on Frequency and Crosstabulation, a clear finding and results are observed. The finding showed that overall customer perception towards marketing programs of POSLAJU can be considered as good even the level of marketing programs effectiveness, customer awareness, customer acceptance and customer satisfaction is still at moderate level. The researcher is also able to give some recommendations and suggestions on how to improve and increase customer awareness, expectations and satisfaction.